Effects of the Combination Training by Self-weight Load Exercises and Dynamic Stretching on Locomotive Abilities in the Middle-aged - Yamanaka, Yuki; Nakanishi, Yasuto; Sato, Yoshiaki; Nakata, Hideomi; Seto, Takayuki (European Journal of Applied Sciences, 2023)
There is a large difference between the healthy and normal life expectancies. Musculoskeletal deterioration and movement disorder are some of the main factors which makes the difference larger. One of main causes for the movement disorder is motor dysfunction due to muscle weakness and a reduced flexibility. Muscle function is improved by strength and/or flexibility trainings. So, it is expected that motor dysfunction can be improved by practicing trainings mentioned above. The present study was designed to investigate the possibilities of self-weight load strength training with dynamic stretching as one of the safe and effective training methods for preventing and/or improving musculoskeletal deterioration and movement disorder. Six middle-aged men (Age 54.3 ± 7.8 yrs) and six middle-aged women (Age 53.5 ±4.0 yrs) participated in the present study. The participants trained for 8 weeks with frequency of three times/week. The training was consisted of forward lunge, one leg squat and a dynamic stretching for hip joints. The stand-up test and 2-step test were performed before and after the eight-week training. The results obtained were analyzed using paired T-tests. 2-step distance was improved by 7.8% after the training (254.6±28.4 cm vs, 237.1±28.4 cm, P < 0.001). Stand-up test was improved by 1.2 points (6.0±1.0 points vs. 4.8±1.3 points, P < 0.001). In the present study we confirmed that stand up and walking abilities, which relate to musculoskeletal deterioration and movement disorder, were improved by combination of self-weight load lower extremity strength exercises (forward lunge and one leg squat) and dynamic stretching.